ASUHAN KEPERAWATAN PADA ANAK DENGAN DIAGNOSA GASTROENTERITIS - Sri Sulastri (Akper Kesdam I/Bukit Barisan Padang, 2019)
Gastroenteritis is an inflammation that occurs in the stomach and intestines, which causes diarrhea with a higher frequency than usual, caused by pathogenic bacteria, viruses and parasites. This type of research is qualitative research with the Stdy Literartue design, data collection is done by the data collection method used in the literary study is the data used comes from the results of research that has been carried out and published in national and international online journals. In conducting a search for research journals published on the internet using Google, Academia, and scholar with the key words: Nursing journals, Research methods literature study Nursing with Gastroenteritis. The results of the study were that children with a diagnosis of gastrorenteritis who experienced CHAPTER 5 times a day accompanied by nausea and vomiting, this usually focused on the client's daily lifestyle who was not clean and lived close to dirty river flow, so from the unclean environment the client got the disease. Gastroenteritis.